The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2158244019893697
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Continued Intention of College Students in China to Use DiDi Mobile Car-Sharing Services

Abstract: This research paper examined the continued intention of college students to use DiDi mobile car-sharing services in China. The unified theory of acceptance and use of technology (UTAUT) was used as the theoretical framework while the data analysis was completed with SPSS. The results have demonstrated that performance expectancy, reliability, efficiency, and security and privacy were significant predictors of the continued intention to use mobile car-sharing services. Contrary to our expectations, effort expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…Wang et al, 2016; Zimmermann & Gerber, 2020) due to rise in an online scam to highlight the challenges connected to the present “authentication schemes,” while others proposed a framework for m-banking verification (Abo-Zahhad et al, 2014; Aithal, 2015; Alhothaily et al, 2018; Basar et al, 2019; Chen et al, 2017; Karim et al, 2020; Nagaraju & Parthiban, 2015; Soviany et al, 2016; Thomas & Goudar, 2018). Similarly, some of the included articles examined m-banking safety and secrecy in general (Cavus et al, 2021; Laukkanen, 2016; Liao et al, 2020; Malaquias & Hwang, 2016, 2019; Mensah et al, 2019; Sharma & Sharma, 2019; Tandon et al, 2018; Thakur & Srivastava, 2015; Y. Wang et al, 2016; Yang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al, 2016; Zimmermann & Gerber, 2020) due to rise in an online scam to highlight the challenges connected to the present “authentication schemes,” while others proposed a framework for m-banking verification (Abo-Zahhad et al, 2014; Aithal, 2015; Alhothaily et al, 2018; Basar et al, 2019; Chen et al, 2017; Karim et al, 2020; Nagaraju & Parthiban, 2015; Soviany et al, 2016; Thomas & Goudar, 2018). Similarly, some of the included articles examined m-banking safety and secrecy in general (Cavus et al, 2021; Laukkanen, 2016; Liao et al, 2020; Malaquias & Hwang, 2016, 2019; Mensah et al, 2019; Sharma & Sharma, 2019; Tandon et al, 2018; Thakur & Srivastava, 2015; Y. Wang et al, 2016; Yang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…(2016); eWOM was from Awad and Ragowsky (2008); and behavioral intention was from Morosan and DeFranco (2016) and Mensah et al. (2019). All the items were rated on a 7‐point Likert scale, as is apt for explanatory research (Joshi et al., 2015; McDaniel & Gates, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The literature has widely identified performance expectancy, effort expectancy, subjective norms, and perceived risk as the main variables of the modified Unified Theory of Acceptance and Use of Technology (UTAUT) model (Mensah et al., 2019; Ooi et al., 2020; Shao et al., 2020). Notwithstanding the numerous studies that have analyzed the factors affecting consumers’ usage intention toward a technology, little is known about the antecedents of on‐demand digital platform adoption (Delgosha & Hajiheydari, 2020; Shao et al., 2020; Yapp et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They highlighted that the commercial sharing domain requires a consideration of perceived product scarcity risk due to rivalry for the shared products such as shared cars. Mensah et al (2019) found that customers' security and privacy protection is an important contributing factor in the engagement with any online service provision or technology. Jing et al (2019) found that perceived risk had a negative impact on behavioral intention to use shared autonomous behavior.…”
Section: ) Individual Factorsmentioning
confidence: 99%
“…Joseph F Hair et al (2006) suggested structure equation modeling (SEM) for analyzing dependent relationships with multiple relationships of dependent and independent variables. Moreover, SEM is widely used for examining the relationships of the variables in TAM model (Barnes & Mattsson, 2017;Fleury et al, 2017;H.Kim et al, 2017;Mensah et al, 2019) .…”
Section: Structural Equation Modelling (Sem)mentioning
confidence: 99%